HIF-1α Mediates TRAIL-Induced Neuronal Apoptosis via Regulating DcR1 Expression Following Traumatic Brain Injury - Fang, Yuanjian; Lu, Jianan; Wang, Xiaoyu; Wu, Haijian; Mei, Shuhao; Zheng, Jingwei; Xu, Shenbin; Lenahan, Cameron; Chen, Sheng; Zhang, Jianmin; Hong, Yuan (Frontiers in Cellular Neuroscience, 2020)
Abstract Background: Neuronal apoptosis involved in secondary injury following traumatic brain injury (TBI) significantly contributes to the poor outcomes of patients with TBI. The tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), can selectively induce apoptosis of tumor cells. Hypoxia factor (HIF) -1α is a controversial factor that mediates the neuronal apoptotic pathway. Herein, we hypothesize that HIF-1α may mediate the TRAIL-induced neuronal apoptosis after TBI. Methods: We used western blots and immunofluorescence to study the expression and cell localization of the TRAIL and death receptor 5 (DR5) after TBI in rats. Soluble DR5 (sDR5) administration was used to block the TRAIL-induced neuronal death and neural deficits. HIF-1α inhibitor 2ME and agonist DMOG were used to study the role of HIF-1α on the TRAIL-induced neuronal death. Meanwhile, HIF-1α siRNA was used to investigate the role of HIF-1α on the TRAIL-induced neuronal death in vitro. Results: The expression of microglia located TRAIL and neuron located DR5 were significantly upregulated after TBI. sDR5 significantly attenuated TRAIL-induced neuronal apoptosis and neurological deficits. 2ME decreased neuronal apoptosis, lesion area, brain edema, and improve neurological function via increased expression of TRAIL decoy receptor 1 (DcR1), which inhibited TRAIL-induced apoptosis after TBI. Administration of DMOG produced the opposite effect of 2ME. Similarly, HIF-1α siRNA attenuated TRAIL-induced neuronal death via increased DcR1 expression in vitro. Conclusion: Our findings suggested that TRAIL/DR5 signaling pathway plays an important role after neuronal apoptosis after TBI. HIF-1α mediates TRAIL-induced neuronal apoptosis by regulating DcR1 expression following TBI.